The Association of the Phylogenetic Typing of the Klebsiella pneumoniae Isolates with Antibiotic Resistance - Shabnam Baghbanijavid; Hossein Samadi Kafil; Safar Farajniya; Seyed Reza Moaddab; Hasan Hosainzadegan; Fatemeh Yeganeh Sefidan; Mojtaba Varshouchi; Hamed Ebrahimzadeh Leylabadlo; Reza Ghotaslou (Emergency Medicine International)
Klebsiella pneumoniae complex (KPC) accounts for approximately one-third of all Gram-negative infections. Moreover, it is highly resistant and can taxonomically be distributed into KpI, KpII, and KpIII phylogroups. This study aimed to investigate the distribution of phylogenetic groups and the relationship between them and antibiotic resistance patterns. For this purpose, we collected KPC isolates from Tabriz, Iran, between 2018 and 2020. Antimicrobial susceptibility testing was performed by disk diffusion agar, and phylogenetic groups were then examined using gyrA restriction fragment length polymorphism (RFLP) and parC PCR methods. A total of 100 KPC isolates were obtained from the clinical specimens (urine, respiratory secretion, blood, wounds, and trachea). The enrolled patients included 47 men and 53 women aged from 1 to 91 years old. The highest sensitivity was found related to fosfomycin as 85%, followed by amikacin as 66%. The three phylogenetically groups by the RFLP-PCR method were found in KPC, 96% (96 isolates) as KpI, 3% (3 isolates) as KpII, and 1% (1isolate) as KpIII. The highest antibiotic resistance was observed in KpI. It was shown that a valid identification of three phylogenetic groups of KPC can be done by combining both gyrA PCR-RFLP and parC PCR. Of note, the KpI group was also observed as the dominant phylogenetic group with the highest resistance to antibiotics.